CeO2 nanoarray decorated Ce-doped ZnO nanowire photoanode for efficient hydrogen production with glycerol as a sacrificial agent. Issue 18 (27th July 2022) - Kim, Seungkyu; An, Eunui; Oh, Inhyeok; Hwang, Jun Beom; Seo, Sehun; Jung, Yoonsung; Park, Jun-Cheol; Choi, Hansol; Choi, Chang Hyuck; Lee, Sanghan
Abstract : Photoelectrochemical (PEC) biomass oxidation by the substitution of an oxygen evolution reaction is considered a promising strategy for efficient hydrogen production. Abstract : Photoelectrochemical (PEC) biomass oxidation by the substitution of an oxygen evolution reaction is considered a promising strategy for efficient hydrogen production. Among the biomass derivatives, glycerol, which is a by-product of biodiesel, is an attractive alternative to water because it is easily oxidized at a potential lower than that of water. In this work, we report a novel CeO2 -decorated Ce-doped ZnO nanowire (NW) photoanode, fabricated via hydrothermal and pulsed laser deposition processes, for efficient PEC glycerol oxidation and hydrogen production. The Ce dopant in the ZnO array improves the charge separation, light-harvesting, and adsorption of glycerol, by providing oxygen vacancies and active sites for PEC water splitting by glycerol. The operation stability of our CeO2 -decorated Ce-doped ZnO NW photoanode is enhanced and its photocurrent density is retained even after 10 h. In addition, the amount of evolved hydrogen produced by the CeO2 /Ce-doped ZnO photoelectrode is two times higher than that of a bare ZnO electrode. Through our results, we confirm the efficient hydrogen evolution via Ce utilization.